2001
DOI: 10.1051/0004-6361:20011120
|View full text |Cite
|
Sign up to set email alerts
|

The extended counterpart of submm source Lockman 850.1

Abstract: Abstract. The IRAM Plateau de Bure mm interferometer and deep K-band imaging have been used to identify the brightest submm source detected in the Lockman field of the UK 8 mJy SCUBA survey. The near infrared counterpart is an extended (20-30 kpc), clumpy, and extremely red object. The spectral energy distribution suggests it to be a dusty star forming object at a redshift of about 3 (2-4). Its star formation rate and nearinfrared properties are consistent with Lockman 850.1 being a massive elliptical in forma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 32 publications
4
75
0
Order By: Relevance
“…The largest survey conducted with Scuba was the SHADES survey (Coppin et al, 2005) covering 0.25 deg 2 to 2 mJy RMS, though several prior surveys at 850µm opened up the discovery space for far-infrared galaxies: the Hawai'i Hubble map with 0.2-4 mJy RMS over 110 arcmin 2 (Barger et al, 1999), the 260 arcmin 2 2.5 mJy RMS 8 mJy survey Fox et al, 2002;Lutz et al, 2001;Almaini et al, 2003;Ivison et al, 2002), the HDF Scan map with 125 arcmin 2 to 3 mJy (Borys et al, 2003), CUDSS with 1 mJy RMS over 60 arcmin 2 (Webb et al, 2003), and the lens survey with 1.7 mJy RMS over 45 arcmin 2 . In the mid-2000's, Mambo began producing similarly fruitful results in Elais N2 and Lockman Hole, with 0.8 mJy RMS over 160 arcmin 2 (Greve et al, 2004), 1 mJy RMS over 400 arcmin 2 in COSMOS , 0.7 mJy RMS over 287 arcmin 2 in GOODS-N (Greve et al, 2008), and 0.75 mJy RMS over 566 arcmin 2 in Lockman Hole North (Lindner et al, 2011).…”
Section: Notable Surveys Focused On Dsfg Discoverymentioning
confidence: 99%
“…The largest survey conducted with Scuba was the SHADES survey (Coppin et al, 2005) covering 0.25 deg 2 to 2 mJy RMS, though several prior surveys at 850µm opened up the discovery space for far-infrared galaxies: the Hawai'i Hubble map with 0.2-4 mJy RMS over 110 arcmin 2 (Barger et al, 1999), the 260 arcmin 2 2.5 mJy RMS 8 mJy survey Fox et al, 2002;Lutz et al, 2001;Almaini et al, 2003;Ivison et al, 2002), the HDF Scan map with 125 arcmin 2 to 3 mJy (Borys et al, 2003), CUDSS with 1 mJy RMS over 60 arcmin 2 (Webb et al, 2003), and the lens survey with 1.7 mJy RMS over 45 arcmin 2 . In the mid-2000's, Mambo began producing similarly fruitful results in Elais N2 and Lockman Hole, with 0.8 mJy RMS over 160 arcmin 2 (Greve et al, 2004), 1 mJy RMS over 400 arcmin 2 in COSMOS , 0.7 mJy RMS over 287 arcmin 2 in GOODS-N (Greve et al, 2008), and 0.75 mJy RMS over 566 arcmin 2 in Lockman Hole North (Lindner et al, 2011).…”
Section: Notable Surveys Focused On Dsfg Discoverymentioning
confidence: 99%
“…Papadopoulos et al 2000). This is comparable to the radio-"quiet" submillimeter source Lockman 850.1, which has been estimated to be at , based on its submillimeter/ 2 Շ z Շ 4 millimeter SED (Lutz et al 2001), as well as other, radio-"loud" galaxies in this redshift range. still within the large observed scatter (see Fig.…”
Section: Identification and Redshift Estimatementioning
confidence: 51%
“…Extrapolation of the steep radio spectrum shows that the contribution of the nonthermal radio emission is negligible at submillimeter wavelengths. For comparison, we overplot a schematic SED representing local ultraluminous galaxies, shifted to (Lutz et al 2001 Serjeant et al 2002) is indicated in Figure 1. WN J0305ϩ3525 was also observed at 1.25 mm using the 37-channel MPIfR Bolometer Array (MAMBO II; Kreysa et al 1998) at the IRAM 30 m telescope on UT 2000 July 18.…”
Section: James Clerk Maxwell Telescope and Iram Observationsmentioning
confidence: 99%
“…There are indications that some millimeter galaxies may be very large and complex objects (Ivison et al 2001;Lutz et al 2001), however. This requires us to state this conclusion precisely: Our astrometry shows that the region emitting the millimeter (dust) emission does not have an optical/near-IR counterpart down to very faint limits.…”
Section: All Three Millimeter Sources Are Blank Fields In the Opticalmentioning
confidence: 99%
“…Much of the later evidence for individual objects (e.g., Lutz et al 2001) and the statistical analysis on the basis of the…”
Section: All Three Millimeter Sources Are Blank Fields In the Opticalmentioning
confidence: 99%